Tolerability of individual chemotherapy regimens in children suffering from respiratory tuberculosis and exposed to multiple and extensive drug resistant tuberculosis - M. F. Gubkinа; Yu. Yu. Khokhlovа; I. Yu. Petrаkovа; N. V. Yukhimenko (Туберкулез и болезни лёгких)
The objective of the study: to assess the tolerability of anti-tuberculosis drugs (TB drugs) in children with respiratory tuberculosis and exposure to multiple and extensive drug resistant tuberculosis treated by individual chemotherapy (CT) regimens.Subjects and methods: Totally, 89 children (2-12 years old) with respiratory tuberculosis, they all were exposed to multiple and extensive drug resistant tuberculosis. Patients were divided into three groups: Group 1 (17 patients) – minor forms, the chemotherapy regimen consisted of 3 TB drugs, Group 2 (35 patients) – limited lesions, the chemotherapy regimen consisted of 4 TB drugs, Group 3 (37 patients) – the disseminated disease, the chemotherapy regimen consisted of 5 TB drugs. The following TB drugs were used in Group 1: Pto ‒ in 94.1%, Z ‒ in 76.5%, PAS ‒ in 76.5%, Am – in 35.3%, E – in 17.6%, and Cs – in 5.9% of cases. In Group 2: PAS – in 94.3%, Z – in 80.0%, Pto – in 68.6%, Am – in 48.6% and Fq – in 45.7%, Cs ‒ in 37.1%, and E – in 25.7% of cases. In Group 3: Z – in 97.3%, PAS – in 89.2%, Pto – in 81.1%, Fq ‒ in 73.0%, Am – in 70.3%, Cs – in 51.4%, and E – in 37.8% of cases.Results. In general, chemotherapy was well tolerated by 50.6% (45 people) of children, and poorly - by 49.4% (44 people), p> 0.05. Toxic reactions were observed statistically significantly more often versus allergic ones: 63.6 ± 7.3% (28 persons) and 36.4 ± 7.3% (16 persons), p < 0.05. The culprits drugs causing toxic reactions were prothionamide (24 patients), pyrazinamide (2 patients), cycloserine (1 patients), and levofloxacin (1 patients), toxic reactions - amikacin (16 patients). Adverse reactions statistically significantly more often occurred when five-component regimen (67.6 ± 7.7%) was used versus three- and four-component regimens (29.4 ± 11.4 and 40.0 ± 8.3%, respectively), p <0.05.